Functional Characterization of the Quorum Sensing Regulator RsaL in the Plant-Beneficial Strain Pseudomonas putida WCS358 - Rampioni, Giordano (American Society for Microbiology, 2012)
In many bacteria, quorum sensing (QS) systems rely on a signal receptor and a synthase producing N-acyl-homoserine lactone(s) as the signal molecule(s). In some species, the rsaL gene, located between the signal receptor and synthase genes, encodes a repressor limiting signal synthase expression and hence signal molecule production. Here we investigate the molecular mechanism of action of the RsaL protein in the plant growth-promoting rhizobacterium Pseudomonas putida WCS358 (RsaL(WCS)). In P. putida WCS358, RsaL(WCS) displayed a strong repressive effect on the promoter of the QS signal synthase gene, ppuI, while it did not repress the same promoter in Pseudomonas aeruginosa. DNase I protection assays showed that purified RsaL(WCS) specifically binds to ppuI on a DNA region overlapping the predicted σ(70)-binding site, but such protection was observed only at high protein concentrations. Accordingly, electrophoretic mobility shift assays showed that the RsaL(WCS) protein was not able to form stable complexes efficiently with a probe encompassing the ppuI promoter, while it formed stable complexes with the promoter of lasI, the gene orthologous to ppuI in P. aeruginosa. This difference seems to be dictated by the lower dyad symmetry of the RsaL(WCS)-binding sequence on the ppuI promoter relative to that on the lasI promoter. Comparison of the results obtained in vivo and in vitro suggests that RsaL(WCS) needs a molecular interactor/cofactor specific for P. putida WCS358 to repress ppuI transcription. We also demonstrate that RsaL(WCS) regulates siderophore-mediated growth limitation of plant pathogens and biofilm formation, two processes relevant for plant growth-promoting activity.